The Use of Advance Technology to Enforce The Dramatic Effects In Modern Cinema - Rikabi, Hany Abd Ali (Journal of Humanities & Social Sciences, 2019)
The cinematic achievement is linked to many scientific techniques that work to achieve the credibility of the visual image. The elements of the cinematic language need to carry out its creative task of some modern techniques and special effects which are often entrusted to convey and embody many of the dramatic and dangerous dramas performed by the characters, real places or fictional places manufactured by modern scientific techniques to verify the impact of the act of dazzling and credibility, so the modern techniques and visual action in the cinematic image is allocated by the researcher, and the research sections to three chapters. In the first chapter after the introduction to the research, the theoretical framework of the research was divided into three sections was the first modern techniques in the film and in the second section, the researcher to the concept of dramatic action, and in the third section discussed the function of modern technologies in the contemporary film. The second chapter (analysis of selected samples) was analyzed and discussed. The third chapter included the most important results of the research and conclusions. After the analysis of the researcher reached a set of results, which found the importance of function modern techniques of various kinds in contemporary film to embody the dramatic act. The software techniques has an active role in building events and actions visually convincing films of assimilation of computer technologies (software and three-dimensional) and include in their work. It was also functioned the idea of mating between what is realistic and what is imaginary through the use of computer software, and based on the researcher that concluded its research in the list of Arabic sources.